PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR IPS KELAS V SDN 09 PONTIANAK TIMUR - Laila Nur Setyaningsih; Sugiyono Sugiyono; Hery Kresnadi (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study was to analyze the influence of the Mind Mapping learning method on the learning outcomes of Social Sciences of fifth grade students of East Pontianak 09th Elementary School. The research method used was an experiment, a form of Quasi Experimental type of non equivalent group design. The study population was all fifth grade students of East Pontianak Elementary School 09 of 100 students. The sampling technique uses purposive sampling. The technique used is direct observation and measurement. Data collection tools in the form of observation sheets and multiple choice tests. The results of data analysis are, the average score of the control class post-test is 56,19 and the experiment is 62,91. Based on the results of the t-test calculation obtained by tcount 2.38>ttable 1.98, then Ha is accepted. This shows that there are differences in the learning outcomes of the control class students with the experimental class. Calculation of effect size is 0.64 with medium criteria. The conclusion of this study is that there is the influence of the Mind Mapping learning method on the learning outcomes of Social Sciences in fifth grade students of East Pontianak 09 Elementary School in the medium category. Keywords: Learning Methods for Mind Mapping, Learning Outcomes, Social Sciences